Variação geográfica e Filogeografia do gênero Hylaeamys Weksler, Percequillo, Voss (2006) (Cricetidae : Sigmodontinae) na Floresta Atlântica. - Brennand, Pamella Gusmão de Góes (2010)
The genus Hylaeamys is considered one of the most complex and diverse of the Sigmodontinae sub-family. They inhabit in evergreen and semi-evergreen forest of cis- Andean tropical and subtropical lowlands and foot-hills from Venezuela and Guianas southward through the Amazonian and the Atlantic rain forest to Paraguay and northern Argentina. Actually seven species can be grouped within that genera but their number and distribuition remains uncertain, especially the number of species in the Atlantic Forest. Analysis of the geographic variation from this species is necessary and justify the relevance of this work. Qualitativy, quantitativy and phylogeographic analyses turn able to observe morphological and geographic variation patterns from different populations through the Atlantic forest. Morphological data corroborate the hypothesis that are two different species in this forest: H. oniscus at the São Francisco Northern bank and H. laticeps at the São Francisco southern bank from southern Bahia to Rio de Janeiro. This work shows that these species are phylogenetically closer to species from western Amazonian rain forest (H .acritus and H. perenensis) than the species that lives in the eastern Amazonian (H. yunganus), and the one living in the dry forests of Cerrado (H. megacephalus). For a better comprehension of the phylogenetically relations between Atlantic Forest species further investigation must be taken including a large number of specimens and collected localities.